JOINT BUSINESS GROUP (KUBE) DEVELOMENT MODEL USING THE MASLAHAH APPROACH (CASE STUDY OF KUBE MEKAR SARI, BENGKALIS REGENCY) - Padlan, Rizky; ,., yusrizal; Harahap, Rahmat Daim (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
AbstractThis study analyzes the development model of the Mekar Sari Joint Business Group (KUBE) in Bengkalis Regency using a maslahah approach. KUBE Mekar Sari, a sewing business entity established in 2021, faces significant challenges in terms of sustainability and independence, particularly related to lax internal management, unsystematic financial management, and minimal member participation and effective external assistance. Using a qualitative approach with a case study method, data was collected through in-depth interviews, observations, and document analysis. Analysis was conducted through the lens of maslahah (maqashid al-syari'ah), encompassing hifz al-Dīn, hifz al-Nafs, hifz al-‘Aql, hifz al-Nasl, and hifz al-Māl. The findings indicate that although KUBE Mekar Sari has internalized ethical values (hifz al-Dīn) and provides work flexibility that supports psychological well-being and family responsibility (hifz al-Nafs and hifz al-Nasl), there is a significant gap in the aspects of asset management (hifz al-māl) and knowledge development/participation (hifz al-‘aql). This study concludes that the KUBE Mekar Sari development model is not yet optimal in achieving holistic well-being due to fundamental weaknesses in internal management and the quality of mentoring. Therefore, it is recommended to strengthen internal management based on maslahah, improve the quality of sustainable mentoring, and develop members' capacity to achieve greater independence and sustainability.Keywords: Cooperative Business Group (KUBE), Maslahah, Economic Empowerment, Case Study, Maqashid al-Syari'ah